2010
DOI: 10.1002/14651858.cd007345.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for patients undergoing elective endoscopic retrograde cholangiopancreatography

Abstract: Prophylactic antibiotics reduce bacteriaemia and seem to prevent cholangitis and septicaemia in patients undergoing elective ERCP. In the subgroup of patients with uncomplicated ERCP, the effect of antibiotics may be less evident. Further research is required to determine whether antibiotics can be given during or after an ERCP if it becomes apparent that biliary obstruction cannot be relieved during that procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 25 publications
2
30
0
6
Order By: Relevance
“…In a Cochrane meta-analysis (9 RCTs, 1573 patients), the prophylactic use of antibiotics was shown to prevent cholangitis (relative risk (RR) 0.54, 95% CI 0.33 to 0.91), septicemia (RR 0.35, 95% CI 0.11 to 1.11), bacteriemia (RR 0.50, 95% CI 0.33 to 0.78), and pancreatitis (RR 0.54, 95% CI 0.29 to 1.00). It was concluded that prophylactic antibiotics reduce bacteriemia and seem to prevent cholangitis and septicemia in patients undergoing elective ERCP (87). Our recommendation is in line with the ASGE recommendation to prescribe antibiotic prophylaxis in procedures where drainage achieved at ERCP is incomplete or achieved with difficulty, such as PSC (88).…”
Section: Esge/easl Suggest Routine Administration Of Prophylactic supporting
confidence: 71%
“…In a Cochrane meta-analysis (9 RCTs, 1573 patients), the prophylactic use of antibiotics was shown to prevent cholangitis (relative risk (RR) 0.54, 95% CI 0.33 to 0.91), septicemia (RR 0.35, 95% CI 0.11 to 1.11), bacteriemia (RR 0.50, 95% CI 0.33 to 0.78), and pancreatitis (RR 0.54, 95% CI 0.29 to 1.00). It was concluded that prophylactic antibiotics reduce bacteriemia and seem to prevent cholangitis and septicemia in patients undergoing elective ERCP (87). Our recommendation is in line with the ASGE recommendation to prescribe antibiotic prophylaxis in procedures where drainage achieved at ERCP is incomplete or achieved with difficulty, such as PSC (88).…”
Section: Esge/easl Suggest Routine Administration Of Prophylactic supporting
confidence: 71%
“…However some meta-analysis and reviews have shown that this strategy was associated with higher rate of postoperative complications [12,13,[19][20][21][22][23]. To access these conflicting opinions, the aim of our study is focused on whether PBD should be performed routinely or selectively in jaundiced patients suffering from pancreatic head cáncer [6,16,19,20,[22][23][24][25][26][27][28].…”
Section: Discusionmentioning
confidence: 99%
“…The American Association of Gastrointestinal Endoscopy guideline stratifies patients according to the procedure, and defines biliary sphincterotomy as a high-risk procedure for bleeding, and ERCP without sphincterotomy as low risk procedure for bleeding. Many studies have proposed diverse ways of preventing these complications related to ERCP, the best one seems to be the consideration of patients comorbidity and the improvement of endoscopist skill [6,16,19,20,[22][23][24][25][26][27][28]. In our collected data from patients files, there was no mention of preoperative ERCP related complications [64].…”
Section: Discusionmentioning
confidence: 99%
“…The use of prophylactic antibiotics before ERCP is therefore recommended by all major international gastroenterological societies, especially in the presence of an obstructed biliary system. [48][49][50] The use of prophylactic antibiotics attempts to decrease or eliminate the incidence of cholangitis, sepsis and pancreatitis after the procedure. [48] During ERCP, bacteraemia is believed to occur because of the injection of contrast and the iatrogenic introduction of foreign substances in the bile of patients who already have underlying pathologies such as biliary obstruction or pancreatic pseudocysts.…”
Section: Acute Cholangitismentioning
confidence: 99%
“…[48][49][50] The use of prophylactic antibiotics attempts to decrease or eliminate the incidence of cholangitis, sepsis and pancreatitis after the procedure. [48] During ERCP, bacteraemia is believed to occur because of the injection of contrast and the iatrogenic introduction of foreign substances in the bile of patients who already have underlying pathologies such as biliary obstruction or pancreatic pseudocysts. Bacteraemia during ERCP is relatively uncommon in patients who do not have evidence of biliary or pancreatic ductal obstruction.…”
Section: Acute Cholangitismentioning
confidence: 99%